Crystal structure of AtGet3 Delta L, a chloroplast Get3 from Arabidopsis thaliana - Manu, M. S.; Ramasamy, Sureshkumar (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Arabidopsis thaliana; Get3; protein targeting

Analysis of tail-anchored protein translocation pathway in plants - Manu, M. S.; Ghosh, Deepanjan; Chaudhari, Bhushan P.; Ramasamy, Sureshkumar (Biochemistry and Biophysics Reports, 2018)
Tail-anchored (TA) proteins are a special class of membrane proteins that carry out vital functions in all living cells. Targeting mechanisms of TA proteins are investigated as the best example for post-translational protein targeting in yeast. Of the several mechanisms, Guided Entry of Tail-anchored protein (GET) pathway plays a major role in TA protein targeting. Many in silico and in vivo analyses are geared to identify TA proteins and their targeting mechanisms in different systems including Arabidopsis thaliana. Yet, crop plants that grow in specific and/or different conditions are not investigated for the presence of TA proteins and GET pathway. This study majorly investigates GET pathway in two crop plants, Oryza sativa subsp. Indica and Solanum tuberosum, through detailed in silico analysis. 508 and 912 TA proteins are identified in Oryza sativa subsp. Indica and Solanum tuberosum respectively and their localization with respect to endoplasmic reticulum (ER), mitochondria, and chloroplast has been delineated. Similarly, the associated GET proteins are identified (Get1, Get3 and Get4) and their structural inferences are elucidated using homology modelling. Get3 models are based on yeast Get3. The cytoplasmic Get3 from O. sativa is identified to be very similar to yeast Get3 with conserved P-loop and TA binding groove. Three cytoplasmic Get3s are identified for S. tuberosum. Taken together, this is the first study to identify TA proteins and GET components in Oryza sativa subsp. Indica and Solanum tuberosum, forming the basis for any further experimental characterization of TA targeting and GET pathway mechanisms in crop plants.

Structure and regulation of SWEET transporters in plants: an update - Anjali, Anjali; Fatima, Urooj; Manu, M. S.; Ramasamy, Sureshkumar; Senthil-Kumar, Muthappa (Plant Physiology and Biochemistry, 2020)
Sugar will eventually be exported transporters (SWEETs), a novel family of sugar transporters found in both eukaryotes and prokaryotes, facilitate sugar flux across the cell membrane. Although these transporters were first discovered in plants, their homologs have been reported in different organisms. SWEETs have critical roles in various developmental processes, including phloem loading, nectar secretion, and pathogen nutrition. The structure of bacterial homologs, called SemiSWEETs, has been well studied thus far. Here, we provide an overview of SWEET protein structure and dynamic function by analyzing the solved crystal structures and predicted models that are available for a few SWEETs in a monocot plant (rice) and dicot plant (Arabidopsis thaliana). Despite the advancement in structure-related studies, the regulation of SWEETs remains unknown. In light of reported regulatory mechanisms of a few other sugar transporters, we propose the regulation of SWEETs at the post-translational level. We then enumerate the potential post-translational modification sites in SWEETs using computational tools. Overall, in this review, we critically analyze SWEET protein structure in plants to predict the post-translational regulation of SWEETs. Such findings have a direct bearing on plant nutrition and defense and targeting the regulation at these levels will be important in crop improvement.
Keywords: oligomerization; Phosphorylation; Post-translational modification; Sugar transporters; Sugar will eventually be exported transporters